Chemostratigraphy and diagenetic constraints on Neoproterozoic carbonate successions from the Sierras Bayas Group, Tandilia System, Argentina - Gómez Peral, Lucia (2007)
Carbon and oxygen isotopic data, combined with a detailed diagenetic study, obtained from undeformed and unmetamorphosed dolomite and limestone from the Neoproterozoic Sierras Bayas Group, Argentina, provide a new record of isotopic stratigraphic variations useful for regional and global correlations. The Sierras Bayas Group is subdivided into the Villa Mónica (sandstones and dolomites), Cerro Largo (siliciclastic rocks) and Loma Negra (limestones) formations, unconformably overlain by the Cerro Negro Formation (siliciclastic rocks with basal marls), and grouped into four depositional sequences bounded by unconformities. The dolomite samples from the Villa Mónica Formation show ranges of δ13C(PDB) values from - 1.3 to + 2.2‰ and of δ13C(PDB) values from - 2.1 to - 6.7‰. Elemental data (Mn/Sr, Fe/Sr and Ca/Sr) and stable isotope compositions point to a moderate to significant degree of diagenetic alteration in samples from this formation. The Loma Negra Formation is composed of homogeneous, non-luminescent micritic limestone with δ13C(PDB) values of samples between + 2.7 and + 4.5‰; δ13C(PDB) values vary from - 7.1 to - 13.5‰. Selected element ratios using Mn/Sr (< 1.4) and Fe/Sr (< 30) combined with C/O isotope data suggest near to primary carbon isotope signatures in these samples. The Villa Mónica Formation can be broadly constrained between 800 and 900 Ma, based on Rb/Sr radimetric data and stromatolite morphologies. The Loma Negra Formation fits in global δ13C and 87Sr/86Sr trends that suggest an age range of ~ 580 - 590 Ma, which is regionally important as it places constraints on the continuity of Vendian basins in south-western Gondwana. In the same sense, the isotopic signatures of Loma Negra Formation samples along with the preservation of a unique shelly fauna make a direct connection of the Argentinian succession to Vendian intervals in Uruguay (Polanco Formation) and Brazil (Corumbá Group). © 2006 Elsevier B.V. All rights reserved.